Microbial diversity in the cecum of broiler chickens after introduction of coumarin and feed antibiotic into the diet - Galimzhan K. Duskaev; Kristina S. Lazebnik; Tatyana A. Klimova (RUDN Journal of Agronomy and Animal Industries, 2022)
In modern world, there is a need to search for alternatives to antibiotics due to the growing resistance of microorganisms. Plant extracts can be a promising replacement. Due to biological functions, they can suppress the development of various processes associated with pathogenicity and virulence, in particular, the Quorum sensing process. Based on the above, the aim of the study was to assess the bioactivity of 7,8-dihydroxy-4- methylcoumarin and 20% chlortetracycline in relation to the microbial diversity of the cecum of broiler chickens. 4 groups of broiler chickens were formed for the experiment. The control group received a diet without additives (basic diet (BD)); group I - BD + 20% chlortetracycline, at the dosage 0.63 g/kg bw per day, group II - BD + 7,8-dihydroxy-4-methylcoumarin at a dose of 9.0 mcg/ kg bw per day; Group III - BD + 7,8-dihydroxy-4-methylcoumarin + 20% chlortetracycline. The NGS of the 16S rRNA gene was used as a research method. Analysis of the results showed that addition of coumarin, the antibiotic and their combination to the poultry diet had an impact on formation of the microbial composition of intestine. Moreover, there was a decrease in the number of Lactobacillaceae , Lachnospiraceae and Erysipelotrichaceae families. In addition, the proportion of opportunistic Streptococcus flora decreased more than by 10 %.